Barbara Johnson's Album: Material Literacy and Consumer Practice, 1746‐1823. (20th March 2019) - Dyer, Serena
Abstract: This article examines Barbara Johnson's Album, a prolific record of the dress consumption of a vicar's daughter. The album contains over a hundred samples of dress fabrics acquired by Johnson between the ages of eight and eighty‐five. Interrogated alongside the Johnson family correspondence and didactic tools produced by Johnson's mother, this article argues that the album acted as a material form of account book, conceived as a moral, financial and material regulator. Considered within the emerging framework of material knowledge and consumer skill, the album provides important evidence of how consumers maintained and developed their material literacy.